Social Capital in Rural Poor Women Entrepreneurship: The Case of Bangladesh - KABIR, Muhammad S.; RADOVIC-MARKOVIC, Mirjana; ISLAM, Monjurul; AKTHER, Rahima; GROZDANIC, Radmila; NIKITOVIC, Zorana (Journal of Advanced Research in Law and Economics; Vol 5 No 1 (2014): JARLE, Volume V, Issue 1(9), Summer 2014, 2017)
This study describes the impact of women entrepreneurship on social capital in their livelihood. The research was conducted on 300 women entrepreneurs in Mymensingh, Bangladesh. The Data was analyzed using ordered probit regression analysis. The following research variables; Contact with other entrepreneurs, leadership in NGOs group meeting, participation in social gathering, political consciousness, water and sanitation were highly and positively associated at (p<.01) with social capital while working experience was at (p<.05) positive and significantly associated with social capital, and changes in Basic needs at (p<.10) also significantly co-efficient with social capital. Among all entrepreneurships, livestock and poultry entrepreneurship is positive and significantly (p<.10) associated with social capital. This implies that livestock and poultry entrepreneurship play significant role in increasing social capital of poor women in rural area of Bangladesh. Whereas formal education and training on different entrepreneurship activities are positive co-efficient with social capital, it’s not significant, hence we can conclude that in rural areas women are not highly educated and they don’t acquire sufficient training facilities due to lack of institutional support.